Role of the Principal in Developing a Culture of Literature and Moral Coaching of Students in Integrated Islamic First Secondary Schools Alkahfi Kabupaten Pasaman Barat - Elfiyenti, Elfiyenti (Program Pascasarjana UMSB, 2024)
This study discusses the role of school principals in developing a culture of literacy and developing morals on students. The issue of student literacy and morals are still the major issue in national education. This low level of students’ literacy turns out to have a negative impact on student development and also makes their future bleak. Developing student morals is an important point that a school principal must also pay attention to so that students have good morals. The principal as a leader and at the same time as a policy holder must have the right strategy. Al Kahfi Integrated Islamic Junior High School, West Pasaman Regency is one of the schools that had promoted literacy as a superior school program. Apart from that, moral development on students is also given great attention so that in the future students will have good character and morals. This study employs a qualitative method with a descriptive approach. Data collection techniques include observation, interviews, and documentation. To ensure data validity, triangulation was utilized. Data analysis involved several steps: compiling, organizing, and synthesizing all field data to draw conclusions. The results of the research showed that the role of the school principal as a manager in developing literacy culture and moral development is by: planning (program planning), organizing (forming a team), actuating (providing guidance) and controlling (evaluating implementation). Meanwhile, the role of the school principal as a leader in developing literacy culture and moral development is to: provide good examples and role models. Meanwhile, as a motivator in developing a culture of literacy and fostering morals, you can: provide rewards to students who excel in the field of literacy and have the best morals.Keyword : Role of school principal, literacy and moral development